Efektivitas Pembelajaran Etnomatematika “Permainan Engklek” Terhadap Pemahaman Konsep Geometri Siswa Sekolah Dasar - Dini Wahyu Mulyasari; Abdussakir Abdussakir; Dewi Rosikhoh (Jurnal Tadris Matematika, 2021)
Mathematics learning in elementary schools frequently encountered obstacles in material delivery. It was due to the abstract concepts of mathematics and the character of students who entered the concrete operational phase. Ethnomathematics learning could become an effort to overcome those obstacles. The purpose of this study was to determined the effectiveness of learning ethnomathematics "engklek-game" on the understanding of geometry concept for third-grade students of SDN 4 Sepanjang Glenmore. This study used a mixed-method approach with the type of experimental research one-group pretest-posttest design. Data collection techniques were through written tests and interviews. The quantitative data were analyzed using descriptive analysis and used paired sample t-test. The qualitative data was analyzed by reducing the data, presenting the data, and drawing conclusions. The results of the study showed that learning ethnomathematics "engklek-game" obtained Sig. (2-tailed) of 0.000, so that it had a significant effect on the understanding of the geometry concept of students in grade III SDN 4 Sepanjang Glenmore. Based on the results of the interview, it found that the student response was good. Teachers stated that students were enthusiastic during the learning, which led to an increase in learning outcomes before and after learning ethnomathematics "engklek-game."